Inhibition of Influenza A Virus (H1N1) Fusion by Benzenesulfonamide Derivatives Targeting Viral Hemagglutinin - Zhu, Lei; Li, Yuhuan; Li, Shaohua; Li, Haodong; Qiu, Zongxing; Lee, Chichang; Lu, Henry; Lin, Xianfeng; Zhao, Rong; Chen, Li; Wu, Jim Z.; Tang, Guozhi; et al. (PLOS ONE, 2011)
Hemagglutinin (HA) of the influenza virus plays a crucial role in the early stage of the viral life cycle by binding to sialic acid on the surface of host epithelial cells and mediating fusion between virus envelope and endosome membrane for the release of viral genomes into the cytoplasm. To initiate virus fusion, endosome pH is lowered by acidification causing an irreversible conformational change of HA, which in turn results in a fusogenic HA. In this study, we describe characterization of an HA inhibitor of influenza H1N1 viruses, RO5464466. One-cycle time course study in MDCK cells showed that this compound acted at an early step of influenza virus replication. Results from HA-mediated hemolysis of chicken red blood cells and trypsin sensitivity assay of isolated HA clearly showed that RO5464466 targeted HA. In cell-based assays involving multiple rounds of virus infection and replication, RO5464466 inhibited an established influenza infection. The overall production of progeny viruses, as a result of the compound's inhibitory effect on fusion, was dramatically reduced by 8 log units when compared with a negative control. Furthermore, RO5487624, a close analogue of RO5464466, with pharmacokinetic properties suitable for in vivo efficacy studies displayed a protective effect on mice that were lethally challenged with influenza H1N1 virus. These results might benefit further characterization and development of novel anti-influenza agents by targeting viral hemagglutinin.